Avaliaç\~ao do FCO estado de Goiás: Ensaio metodológico - Murilo José de Souza Pires; Ronaldo Ramos Vasconcellos; Gislaine de Miranda Quaglio; Rodrigo Portugal (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– The Constitutional Funds were established by art. 159, item I, paragraph c of the Federal Constitution of 1988 with the objective of contributing to the "reduction of inequalities" existing between the peripheral regions of the North, Northeast and Center-West vis-à-vis the central regions of the Southeast and South. In this sense, its role as a financier of productive investments in these peripheral regions has increased in recent decades. Thus, the objective of this investigation was to understand the profile of spatial associations in the cities of Goiás through some economic variables. Additionally, to verify how the variables FCO and GDP per capita behaved in certain regions with different profiles in the period from 2002 to 2018. Therefore, the argument woven in the work started from the premise that the productive structure of Goiás is marked, by its historical formation and economic, due to a structural heterogeneity that sets limits to the reach and depth that impulses from the modernization process can reach the productive systems of agricultural units and industrial sectors in the state of Goiás. quali-quantitative that aimed to unveil the regularities and uniformities of the phenomenon related to disbursements in the FCO in the productive structures of the immediate regions of Goiás in the period from 2002 to 2018. Finally, it is observed that, in nominal values, the directed resources of the FCO for the immediate regions in Goiás corroborate the evidence presented by the economic literature. what is about the FCO, that is, that they point to a concentration in those regional spaces with greater economic dynamism. On the other hand, when the behavior of these disbursements is observed, in terms of variations, it appears that, even marginally, FCO resources are stimulating changes in the productive structures of immediate regions that are still rooted in traditional and subsistence economies as is the case of Flores de Goiás.
Keywords: R11; 330; Constitutional Fund of the Midwest; structural heterogeneity; Goiás